Innovating Assessment for Grade VII Arabic Curriculum: A Design–Development Study of Ministry Textbooks - Nurhikmah Sani; Dewi Rahayu; Vikky Alziqri JH; Irhamudin Irhamudin; Zikri Rahman (Fakultas Tarbiyah dan Keguruan, 2026)
Purpose – This study aimed to identify shortcomings in the Grade VII Arabic teaching materials issued by the Ministry of Religious Affairs and to develop an improved, curriculum-aligned assessment prototype that supports student accessibility and instructional diagnosis. Design/methods/approach – A Design and Development Research (DDR) approach guided three integrated phases—needs analysis (document review and teacher interviews), prototype design, and expert validation—using a curriculum-evaluation checklist and iterative revision cycles. The analysed textbook authored by Faruq Baharudin and edited by Wahib Dariyadi was systematically mapped for item typology and skill coverage, revealing consistent lesson structures but predominant reliance on written, pragmatic items. Findings – Results indicated a pronounced gap in listening assessment, which emphasized letter- and word-level discrimination and dictation while underrepresenting sentence- and discourse-level comprehension; expert validation produced high I-CVI scores for many items and recommended explicit item-to-competency mapping, graded difficulty markers, and rubric-guided performance tasks. Prototype revisions incorporated sentence-level listening prompts, short-dialogue response items, and rubric-guided speaking and writing assessments to broaden construct coverage and diagnostic capacity. Research Implications – The study implies that curriculum designers, teacher educators, and policymakers should prioritize item-competency alignment, targeted teacher professional development, and modest ICT provisions to realize performance-based assessment benefits. Limitations include reliance on document analysis, interviews, and expert validation without large-scale classroom trials, and the paper recommends phased pilot testing with mixed-methods evaluation to establish effectiveness and scalability.